The Effect of Luxury Brand and Brand Experience on Customer Loyalty (Coach Brand Case Study) - Anggi Lestari; Perkasa , Didin Hikmah (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of brand luxury and brand experience on customer loyalty among Coach consumers in Indonesia. A quantitative survey of 200 respondents (purposive sampling) was analyzed using PLS-SEM (SmartPLS 4). The results show that brand luxury positively and significantly affects loyalty (β=0.382; t=3.936; p<0.001), and brand experience also has a positive significant effect and is slightly stronger (β=0.407; t=3.915; p<0.001). The findings indicate that luxury cues (quality, prestige, exclusivity) and a consistent brand experience increase repurchase intention, recommendations, and long-term commitment. Managerially, brands should sustain their luxury positioning while designing superior customer experiences across all touchpoints.